Pengujian Mobile Service Quality Terhadap Continuance Intention: Perceived Value Sebagai Variabel Mediasi - Rifkiyanda Mulyasa , Haikal; Tjahyadi, Rully Arlan (Coopetition : Jurnal Ilmiah Manajemen, 2025)
The growth of technology has led to the development of various MVAS forms available by mobile telecommunication companies, which has made the existence of MVAS in Indonesia increasingly popular. This study aims to examine the influence of mobile service quality on perceived value and continuance intention, the influence of perceived value on continuance intention, and the role of perceived value as a mediating variable in the relationship between mobile service quality and continuance intention. There are 150 MVAS consumers as the sample size for this study. The sample collection uses a non-probability method with purposive sampling technique. Validity and reliability tests were applied to test the study instruments. The data were tested using classic assumption tests: multicollinearity test, heteroscedasticity test, and normality test. Hypothesis testing was conducted using the Path Analysis method. The study found that mobile service quality influences perceived value. Other results indicate that mobile service quality and perceived value influences continuance intention. Additionally, perceived value is known to partially mediate the indirect relationship between mobile service quality and continuance intention. This study is expected to provide answers to the limitations of previous studies. The managerial implications of this research are expected to contribute to mobile telecommunication companies.